Evaluation of the heterostructure ITO/BiVO4 under blue monochromatic light irradiation for photoelectrochemical application - da Silva Pelissari, M. R. [UNESP]; Scalvi, L. V.A. [UNESP]; Neto, V. S.L.; Dall’Antonia, L. H. [UNESP] (Springer Nature, 2020)
In this paper, the semiconductor material BiVO4 was obtained by an adapted process of solution combustion synthesis, using poly(ethylene glycol) (PEG 6000) as an additional stabilizing agent, and deposited on indium-doped tin oxide (ITO) substrate, by the dip-coating deposition process, to build an ITO/BiVO4 thin film heterostructure, which can be used as photoanode in photoelectrochemical (PEC) cell. The ITO/BiVO4 photoanode has its performance evaluated by linear sweep voltammetry (LSV), chronoamperometry, and electrochemical impedance spectroscopy (EIS) techniques, under blue monochromatic light, provided by an InGaN LED source. The LSV curve shows that the photoactivity of the photoanode presents a drastic jump in the current density under illumination and negligible dark current density. Reproducibility of the electrode photoactivity is observed under light-chopped illumination. The decay profile of photocurrent suggests that despite of charge carriers recombination process occurring in the ITO/BiVO4 electrode, it still presents good photoelectrocatalytic efficiency. Additionally, the long-term current stability indicates that the current density stays stable, without considerable decay, for at least one hour. The steady-state photocurrent density obtained is equal 91 µA cm− 2. EIS results showed that under illumination, the charge transfer resistance (Rct) is considerably lower than the dark condition. The PEC performance evaluated for discoloration reaction in rhodamine B (RhB) and methylene blue (MB) shows that the photoelectrochemical system is quite efficient.